Effect of Crumb Rubber by Partial Replacement on Compressive Strength and Flexural Strength of Concrete (International Journal of Innovative Research in Engineering & Management, 2023)
The utilization of discarded rubber tires  contributes to environmental protection and helps in  preserving natural aggregates. The proper disposal of  waste materials is a significant global concern. The  management of waste tires poses a major challenge since  this material decomposes very slowly over time. For this  universal concern, significant research inquiries have been conducted to explore diverse applications of rubber  derived from tires crumb rubber. Across the globe are actively pursuing alternative substancesthatare economical and for the conservation of limited natural  resources such as sand and aggregate. The focal point of this research involves the partial  replacement of fine aggregate (by weight) with crumb  rubber in M-25 and M-35 grade concrete mixes at various  percentages: 0%, 5%, 10%, and 15%.
Keywords: Replacement; Crumb; Compressive; Flexural